New developments of formability evaluation methods for hot stamping. Issue 1 (1st December 2022) - Li, J; Cheng, Q; Zhang, R; Shi, Z; Lin, J
Abstract : Formability is an essential material property that needs to be considered when selecting materials for hot stamping applications. Due to the difficulties of achieving rapid cooling before deformation and the failure of lubricant systems, however, it is challenging to use conventional Nakajima and Marciniak tests to evaluate the formability of materials under hot stamping conditions. Recently, biaxial test methods have shown great potential to overcome this challenge. In this paper, recent developments of the biaxial test methods for formability evaluation are reviewed, including testing machines, specimen designs, specimen heating methods, testing procedures, and limit strain determination methods. Compared to the Nakajima or the Marciniak tests, the biaxial test method can provide better simulation for hot stamping conditions and it can be a promising method for evaluating the formability of sheet metals under hot stamping conditions. However, more developments such as the standardisation of the specimen designs and the limit strain determination methods, are still needed for the wide use of the biaxial test method.